2014
DOI: 10.1007/s10157-014-1049-z
|View full text |Cite
|
Sign up to set email alerts
|

Is the mean platelet volume a predictive marker for the diagnosis of acute pyelonephritis in children?

Abstract: The MPV is a fast and reliable measurement with considerable predictive value for the diagnosis of APN and renal scars, and its predictive capacity is better than that of CRP, ESR, and WBC values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
33
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 21 publications
(20 reference statements)
8
33
5
Order By: Relevance
“…9 This is in accordance with Catal et al who demonstrated that the platelet counts were higher in patients with upper UTI and MPV values were higher in Gram-positive infections compared with Gram-negative infections. 10 He speculated that the rise in MPV in UTI can be caused by increased production of larger and /or younger platelets as a reaction to infection related platelet destruction, and increased level of beta-thromboglobulin in bacterial infection might activate and release platelet.…”
Section: Discussionsupporting
confidence: 82%
“…9 This is in accordance with Catal et al who demonstrated that the platelet counts were higher in patients with upper UTI and MPV values were higher in Gram-positive infections compared with Gram-negative infections. 10 He speculated that the rise in MPV in UTI can be caused by increased production of larger and /or younger platelets as a reaction to infection related platelet destruction, and increased level of beta-thromboglobulin in bacterial infection might activate and release platelet.…”
Section: Discussionsupporting
confidence: 82%
“…Tekin M investigated the MPV role in acute pyelonephritis (APN) and found that MPV is a fast, reliable standard that can adequately predict the APN diagnosis and renal scars. MPV is a better predictive factor than CRP, ESR, and WBC values (15). In our study, MPV was lower in the patients with AKI with criteria of loss and failure than in patients with other criteria of AKI.…”
Section: Discussionsupporting
confidence: 38%
“…MPV and Some Other Infectious Diseases: MPV levels were higher in children with APN than in those with lower urinary tract infection, but its predictive capacity compared with CRP in children with APN is debated [13,15]. MPV levels have been found higher in cirrhotic patients with AFI than in those without bacterial infection or in healthy controls [16,28].…”
Section: Mpv and Brucellosismentioning
confidence: 99%
“…myocardial infarction, ischemic stroke, mesenteric ischemia, deep vein trombosis, decompansated heart failure) or infectious diseases [e.g. sepsis, infective endocarditis, pneumonia, brucellosis, cellulitis, acute pyelonephritis (APN), ascites fluid infection (AFI), hepatitis B or hepatitis C] [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
mentioning
confidence: 99%